An investigation of the effects of plasma-heating on the resistive-driven filamentation modes - Khanzadeh, H.; Mahdavi, M. (Chinese journal of physics (Taipei), 2021)
•The effects of plasma heating on the resistive filamentation modes have been studied.•The plasma heating effects are restricted to the J×B pinching and the Nernst effect.•The dispersion relation is derived based on the kinetic theory by Ohm’s law.•The growth rate of the resistive filamentation instabilities is derived analytically.•Results are investigated in the inertial confinement fusion (ICF) subjects. In the field of fast ignition schemes, it is possible to heat the plasma during the injection of the relativistic electron beams. This might be strongly effective in the self-generated magnetic fields and divergence of the relativistic electron beams in the transport process. In this paper, the effects of plasma heating, J×B pinching, and Nernst (arising from the hot electrons flux) on the resistive filamentation modes in a magnetized anisotropic plasma were investigated. Results showed a significant reduction of the instability growth rate. Findings suggested that the reconnection and convection of the magnetic field lines could change the intensity of the collimation coefficient of the electron beams. In addition, the instability could exist in a safe mode even when the plasma entered an isotropic condition, compared to the temperature anisotropy-driven instabilities, where this could be affected by the relativistic electrons mean velocity.